2017
DOI: 10.1186/s12884-017-1498-y
|View full text |Cite
|
Sign up to set email alerts
|

Abortion as empowerment: reproductive rights activism in a legally restricted context

Abstract: BackgroundThis paper analyzes the strategies used by activist health professionals in Argentina who justify providing abortion despite legal restrictions on the procedure. These “insider activists” make a case for abortion rights by linking pregnancy termination to a woman’s ability to exert agency at a key point in her reproductive life, and argue that refusing women access to the procedure constitutes a grievous health risk. This argument frames pregnancy termination as an issue of empowerment and also as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 24 publications
0
15
0
15
Order By: Relevance
“…Such decisions are essential because sexual interactions often encompass complex, iterative sexual decision-making processes that challenge women to make a multitude of situational appraisals and engage in a variety of sexual behaviors [15]. According to Prata, Tavrow and Upadhyay [16] and McReynolds-Pérez [17], women’s decision making is essential in their reproductive choices because the choices they make on their reproductive health are critical for them to live a better life. Studies have shown that in countries where women have issues with reproductive health decision-making, unwanted pregnancies and unsafe abortions are high [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Such decisions are essential because sexual interactions often encompass complex, iterative sexual decision-making processes that challenge women to make a multitude of situational appraisals and engage in a variety of sexual behaviors [15]. According to Prata, Tavrow and Upadhyay [16] and McReynolds-Pérez [17], women’s decision making is essential in their reproductive choices because the choices they make on their reproductive health are critical for them to live a better life. Studies have shown that in countries where women have issues with reproductive health decision-making, unwanted pregnancies and unsafe abortions are high [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…The history of MA shows us how informal networks have discovered, shared and created the space for SMA to flourish, from Brazilian womxn in the 1980s discovering misoprostol as an abortifacient 67 to the Abortion Without Borders coalition in 2020. 20 They have not just enabled the “strategic life choices which are critical for people to live the lives they want” 68 but have created spaces for innovation, hope and joy. It is these actors who have pushed for the shifts we now see in formal service provision, who have paved the way for better quality care and access.…”
Section: Discussionmentioning
confidence: 99%
“…Feminism and women’s activism influenced the social arena with their contentious actions, the legal context with their legal activism, and the healthcare facilities’ and providers’ actions with their insider activism. 23 , 24 Their strong collaboration also resulted in the formation of public policies and the drafting of ministry of health guidelines.…”
Section: Discussionmentioning
confidence: 99%